Honey as a risk factor for erythema multiform: case report: Madu sebagai faktor risiko eritema multiform: laporan kasus - Ani Megawati; Tenny Setiani Dewi (Makassar Dental Journal, 2022)
Erythema multiform (EM) is an acute and recurrent hypersensitivity reaction that occurs on the skin and oral mucosa. EM's risk factors include viral infections,drugs, radiation, autoimmune diseases, foodstuffs, and chemicals. Various bee products such as propolis, honey, and bee pollen are believed to have therapeutic effects for various diseases but can trigger allergic reactions. A 31-year-old female patient came to the Oral Medicine clinic with swollen and bleeding lips 2 weeks ago. The patient initially felt her lips were dry and exfoliate, then smeared her lips with honey but they became swollen and painful. The patient felt itchy on hertongue after consuming honey a few months ago. Clinical examination showed edema accompanied by erosive lesions, and ulcers, tend to bleed hemorrhagic crusts on the upper lip to the upper labial mucosa and lower lip. Laboratory examination showed IgE titer increased fourfold, IgG and IgM anti-HSV-1 were negative. The diagnosis was erythema multiforme. The therapy given is 0.9% NaCl compress on the lips using sterile gauze, applying topical corticosteroids to the lips, and educating the patient to not use and consume honey or other bee products. The patient recovered without scarring after two weeks of therapy. It was concluded that honey can be a risk factor for the emergence of EM, so it is very important to eliminate risk factors for the management and prevention of EM recurrence.